A multi-proxy μ-XRF inferred lake sediment record of environmental change spanning the last ca. 2230 years from Lake Kanono, Northland, New Zealand. (1st December 2019) - Evans, Gianna; Augustinus, Paul; Gadd, Patricia; Zawadzki, Atun; Ditchfield, Amber
Abstract: Reliable interpretation of annual-resolution climate proxies for wind, precipitation, and detrital influx are required for identifying the onset and periodicities of climatic events. In particular, this is essential for the evaluation of inter-annual, decadal, and centennial trends driven by shifting positions of the Southern Westerly Winds (SWW) and subsequent storm belts associated with the Southern Annular Mode (SAM) and El Niño Southern Oscillation (ENSO). Here we present a quasi-annual data set of μ-XRF time series spanning ca. 2230 years from lake sediment cores from Lake Kanono, Northland, New Zealand. The μ-XRF time series were interpreted using a combination of principal component analysis (PCA) and cluster analysis, then verified with comparison to regionally averaged empirical rainfall and wind climate station data. Our results show that the wavelet patterns align with the PCA results allowing the μ-XRF time series to be classified into: Group I (detrital) and Group II (biological productivity and normalized climate proxies). The normalized Group II μ-XRF time series wavelet analyses displayed periodicities in the 2–16 year frequency, likely associated with ENSO, from ca. 237 BCE – 1330 CE. The data show clear evidence of both Polynesian and European settlement phases in this part of northern New Zealand, and that Polynesian settlement impact was coeval with changes in ENSO intensity and a phase shift in SAM ca. 1350 CE. The Medieval Climate Anomaly (MCA) and the Little Ice Age (LIA) appear in the μ-XRF time series data as separate clusters. This data suggests that the MCA is associated with windy/dry conditions with intermittent storminess. During the LIA, the 2–16 year periodicity associated with ENSO decreased and centennial to multi-decadal length periodicities increase, which may be an indication of an underlying SAM signal within the data. European settlement also had a direct impact on the lake basin via increased detrital influx, likely from farming activities and intensification of local forestry operations. Highlights: Verification of μ-XRF data interpretation with empirical climate station data. The MCA is associated with windy/dry conditions with intermittent storminess. Reduced ENSO signal during the LIA suggests an underlying multi-decadal SAM signal. Polynesian settlement was coeval with changes in ENSO and a phase shift in SAM.